2014
DOI: 10.1186/1751-0759-8-10
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal specific anxiety in irritable bowel syndrome: validation of the Japanese version of the visceral sensitivity index for university students

Abstract: ObjectiveThe visceral sensitivity index (VSI) is a useful self-report measure of the gastrointestinal symptom-specific anxiety (GSA) of patients with irritable bowel syndrome (IBS). Previous research has shown that worsening GSA in IBS patients is related to the severity of GI symptoms, suggesting that GSA is an important endpoint for intervention. However, there is currently no Japanese version of the VSI. We therefore translated the VSI into Japanese (VSI-J) and verified its reliability and validity.Material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
41
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 40 publications
6
41
0
Order By: Relevance
“…Furthermore, the administration of a CRH receptor antagonist inhibited this exaggerated response in IBS subjects, and also decreased self-reported pain scores during electrical rectal stimulation in IBS subjects (Fukudo et al, 1998). Similarly, we found that the major alleles for the CRH-R1 SNPs were associated with GI symptom anxiety as measured by VSI, which has been shown to positively correlate with IBS severity in both U.S (Labus et al, 2007) and Japanese (Saigo et al, 2014) cohorts of IBS subjects, further suggesting that CRH receptor activation results in increased visceral perception. The presence of general trauma events early in life impacted the association of one of the CRH SNPs and usual IBS symptom severity, but only in IBS subjects with at least one copy of the minor allele of CRH-R1 SNP, rs110402.…”
Section: Discussionsupporting
confidence: 54%
“…Furthermore, the administration of a CRH receptor antagonist inhibited this exaggerated response in IBS subjects, and also decreased self-reported pain scores during electrical rectal stimulation in IBS subjects (Fukudo et al, 1998). Similarly, we found that the major alleles for the CRH-R1 SNPs were associated with GI symptom anxiety as measured by VSI, which has been shown to positively correlate with IBS severity in both U.S (Labus et al, 2007) and Japanese (Saigo et al, 2014) cohorts of IBS subjects, further suggesting that CRH receptor activation results in increased visceral perception. The presence of general trauma events early in life impacted the association of one of the CRH SNPs and usual IBS symptom severity, but only in IBS subjects with at least one copy of the minor allele of CRH-R1 SNP, rs110402.…”
Section: Discussionsupporting
confidence: 54%
“…It is unlikely that participants selected by physicians may be biased since physicians were asked to exclude FGID patients who had improved their GI symptoms and the mean severity score in IBS patients was considered as a moderate level at the index visit on the IBS-SSS, 13 which was almost concordant with the previous findings of validation studies for IBS. 9,23,24 Lastly, IBS patients were significantly younger in age compared with FD patients or control subjects. Younger population might be more educated than older population in Japan.…”
Section: Discussionmentioning
confidence: 99%
“…Visceral Sensitivity Index is a 15‐item questionnaire designed to measure visceral sensitivity and gastrointestinal‐specific anxiety. The total score ranges from 0 ( no gastrointestinal‐specific anxiety or visceral hypersensitivity ) to 75 ( severe gastrointestinal‐specific anxiety and visceral hypersensitivity ).…”
Section: Methodsmentioning
confidence: 99%